225k views
3 votes
If f(x) = 3x + 2 and g(x) = x2 – x, find each value.
16. g(2) =
g(2) =

User Max Song
by
5.6k points

2 Answers

2 votes

Answer:

g(2)=2

Explanation:

g(x)=x2-x

First you have to substitute.

g(2)=2(2)-2

Now just solve.

g(2)=2

User Valegians
by
5.3k points
3 votes

Answer: 2

Work Shown:

g(x) = x^2 - x

g(2) = 2^2 - 2 ... replace every x with 2

g(2) = 4 - 2

g(2) = 2

In this case, we won't use f(x)

User Danke Xie
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.